Análisis de variabilidad de precipitación, temperatura y evapotranspiración en la subcuenca del río Chambo, período 1960-2021 - Cevallos Barragán, Marcelo Roberpierre (2023)
The study focuses on the analysis of the variability of precipitation, temperature and evapotranspiration of the sub-basin of the Chambo river period 1960-2021. The objective of this research is to obtain data from weather stations considering that most of the stations had missing data, for which, through data filling techniques, from satellite data from Google Earth Pro and NASA POWER applications. For the reliability of the filled data, a correlation analysis and the coefficient of determination R2 were performed, once they met the acceptance criteria of the coefficients, a database with temperature information was structured, precipitation and evapotranspiration, which was obtained with the Thorn Thwaite method. In addition, spatial multitemporal analysis of database variables was performed, this through anomaly analysis by means of trend charts, and then through the geostatistical method Kriging generate the monthly thematic maps of each year of study. In this context, in the eighties there was an increase in the values of all parameters due to the "El Niño" phenomenon according to the data analyzed; On the other hand, in 2005 there was a sharp change and parameters decrease due to the presence of the "La Niña" phenomenon.